Overcoming Barriers to Youth Economic Inclusion in Rural Morocco: A Case Study of Daït Aoua - Mohamed Taha Lahrech; Bochra Makhlouki; Younes Bekkar; Imane Bounadi; Rachid Harbouze; Nassreddine Maatala; Julien Burte (Societies)
In rural areas like the Daït Aoua territory, young people often face economic marginalization due to limited access to land, financial resources, and socio-cultural constraints. This study examines the economic inclusion of youth in this region and identifies key factors influencing their participation in local economies. Using a participatory territorial approach, we combined quantitative and qualitative data through surveys, interviews, and statistical analyses. The findings highlight significant spatial inequalities restricting youth to low-income, precarious roles in agricultural labor or unpaid family work, primarily due to delayed intergenerational land transfers. Despite some efforts toward income diversification through entrepreneurship and seasonal migration, these strategies are often hindered by a lack of capital and market limitations. The research underscores the need for targeted policies to address these structural barriers, promote equitable access to resources, and foster sustainable economic development. Understanding these dynamics is essential for creating opportunities that empower rural youth, enabling them to contribute meaningfully to their communities’ growth.